How can I Write Other? The Pains and Possibilities of Autoethnographic’s Research Writing Experienced by a non-Western Female Student - Andriani, Dewi (Journal of International Students, 2022)
In this paper, I am going to explore an other kind of research writing by sharing my research journey as a PhD female student from a non-Western background experiencing research differently. Starting my study within a standard conventional methodology, I shifted my research to a non-traditional mode of doctoral research writing called autoethnography. I employ writing as a method of inquiry (Richardson & St Pierre, 2005) where I can center my voice, write creatively and move beyond normative, positivist and post-positivist paradigms. Following this autoethnographic path, I experienced struggles and opportunities to endeavor to push my writing beyond the limit in the field of play in a language which is not my first language.